2010
DOI: 10.1136/thx.2010.136242
|View full text |Cite
|
Sign up to set email alerts
|

A simple, valid, numerical score for grading chest x-ray severity in adult smear-positive pulmonary tuberculosis

Abstract: BackgroundThe grading of radiological severity in clinical trials in tuberculosis (TB) remains unstandardised. The aim of this study was to generate and validate a numerical score for grading chest x-ray (CXR) severity and predicting response to treatment in adults with smear-positive pulmonary TB. Methods At a TB clinic in Papua, Indonesia, serial CXRs were performed at diagnosis, 2 and 6 months in 115 adults with smear-positive pulmonary TB. Radiographic findings predictive of 2-month sputum microscopy statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
214
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(249 citation statements)
references
References 25 publications
14
214
3
2
Order By: Relevance
“…Heavily blood-stained samples were excluded from the study. A chest X-ray (CXR) scoring system was devised, derived from published scoring systems (31)(32)(33)(34)(35). Zero to three points were scored reflecting the absence of cavities, presence of cavities of Ͻ2 cm, cavities of 2 to 4 cm, and cavities of Ͼ4 cm in size respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Heavily blood-stained samples were excluded from the study. A chest X-ray (CXR) scoring system was devised, derived from published scoring systems (31)(32)(33)(34)(35). Zero to three points were scored reflecting the absence of cavities, presence of cavities of Ͻ2 cm, cavities of 2 to 4 cm, and cavities of Ͼ4 cm in size respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies that involved the grading of chest radiographs were excluded, as these studies were designed to grade the severity of PTB based on the extent of abnormalities visualised on the chest radiograph and not the diagnostic accuracy of scoring systems [55][56][57][58][59]. We also excluded three studies that used the Chest Radiograph Reading and Recording System (CRRS) [60][61][62], despite these studies demonstrating the CRRS tool to have good reliability for features of PTB visualised on a chest radiograph, as these studies did not use culture as a reference standard.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Dawson et al [27] founded similar results (K = 0.32) between radiologists in South Africa. Anna Ralph et al [28] observed low concordance (K = 0.12) between radiologists in Australia. In our study, observers were generally more consistent for the detection of nodules than for the detection of caverns even if individual performances were better in the detection of caverns.…”
Section: Discussionmentioning
confidence: 99%